Benefits of vitamin C use in the septic patient: how well does the evidence support this indication? - Arana-Restrepo, Vanesa (2024)
Objective: to summarize and analyze the most recent evidence on the effect of vitamin C administration in patients with sepsis. Methods: narrative review. A literature search was conducted using the search terms "Vitamin C" and "Sepsis," along with synonyms, which were combined using the "AND" and "OR" operators in the PubMed, ScienceDirect, Web of Science, and MEDLINE databases. Results: based on recent cellular and molecular studies, it has been demonstrated that vitamin C has antioxidant, anti-inflammatory, and antimicrobial properties, suggesting potential benefits in sepsis. While some randomized controlled trials have found an increased risk of up to 20% in mortality or persistent organ failure, others have observed a decrease in mortality of up to 40%, as well as reduced hospital stay and mechanical ventilation duration. Conclusion: to date, the evidence is heterogeneous regarding the potential benefit of intravenous vitamin C as monotherapy or combination therapy in the management of patients with sepsis or septic shock. While randomized controlled trials may suggest no benefit, particularly in terms of mortality or persistent organ failure at 28 days, some meta-analyses tend to show a reduced risk of death. Therefore, further evidence is still needed to provide a broader understanding of this issue.